Risk perception dan anchoring dalam pengambilan keputusan investasi - Rico Limgestu; Yulfiswandi; Alvin; Nopry; Ilianto Tri Sagianto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Investors may not always think logically based on real events; they sometimes think irrationally. Investor decisions can be based on illogical reasoning Psychological biases influence thinking, which can often lead to poor judgment in Financial Behavior when investing something. This study aims to determine the effect of anchoring and risk perception on the investment decisions of Indonesian sharia investors. This research uses quantitative research methods. The sampling method uses simple random sampling, and the data collection method is from a questionnaire survey. Descriptive analytical sampling and structural equation modeling were used to analyze the data (SEM). The findings reveal this anchoring variable has a positive impact on investment decision making on Sharia investors in the city of Batam. Then this risk perception variable also has a positive impact on investment decision making on Sharia investors in the City of Batam.